ZAT10 plays dual roles in cadmium uptake and detoxification in Arabidopsis - Dang, Fengfeng; Li, Yajing; Wang, Yanfeng; Lin, Jinhui; Du, Shenxiu; Liao, Xinyang (Frontiers in Plant Science, 2022)
Cadmium (Cd) is a harmful heavy metal that is risky for plant growth and human health. The zinc-finger transcription factor ZAT10 is highly conserved with ZAT6 and ZAT12, which are involved in Cd tolerance in plants. However, the definite function of ZAT10 in Cd tolerance remains uncertain. Here, we demonstrated that ZAT10 negatively regulated Cd uptake and enhanced Cd detoxification in Arabidopsis. The expression of ZAT10 in plants is induced by Cd treatment. The zat10 mutant plants exhibited a greater sensitivity to Cd stress and accumulated more Cd in both shoot and root. Further investigations revealed that ZAT10 repressed the transcriptional activity of IRT1, which encodes a key metal transporter involved in Cd uptake. Meanwhile, ZAT10 positively regulated four heavy metal detoxification-related genes: NAS1, NAS2, IRT2, and MTP3. We further found that ZAT10 interacts with FIT, but their regulatory relationship is still unclear. In addition, ZAT10 directly bound to its own promoter and repressed its transcription as a negative feedback regulation. Collectively, our findings provided new insights into the dual functions of ZAT10 on Cd uptake and detoxification in plants and pointed to ZAT10 as a potential gene resource for Cd tolerance improvement in plants.